(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
Today, it is necessary to deepen research on the factors causing poverty in our country and their causes. This article is based on the research status of the theory of the formation of poverty and tries to propose it together with practical experience. It is based on analytical guidelines that reveal the internal logical connections between the various factors that cause poverty. At the same time, the current state of research on the mechanism of poverty reduction is revealed.